Approaching chronic problems in primary-care using the task-oriented processes in care (TOPIC) - Ramal-Moreno, Jojay S (2020)
The integrative approach to care for patients demands training to evaluate frequent chronic problems in the outpatient clinic. Patients with hypertension, diabetes mellitus and asthma can be approach using models of evaluations such as the TOPIC that allows to order the evaluations in a structured sequence of four mayor tasks: processing of the information, development of an adequate physician-patient-family relationship and integrating information and learning for life. Processing information implies four sub-activities in which we evaluate patient´s expectations and concerns, severity and control of conditions, adherence and side effects of treatments focusing on damage to target organs and comorbidities. Applying this model can help physicians and their patients to be more efficient in managing chronic problems considering the short time available for ambulatory care.